2020
DOI: 10.1101/2020.03.16.991273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of skeletal protein preparation for LC-MS/MS sequencing yields additional coral skeletal proteins inStylophora pistillata

Abstract: 14Stony corals generate their calcium carbonate exoskeleton in a highly controlled 15 biomineralization process mediated by a variety of macromolecules including 16 proteins. Fully identifying and classifying these proteins is crucial to understanding 17 their role in exoskeleton formation, yet no optimal method to extract and isolate and 18 characterize coral skeletal proteins has been established and their complete 19 composition remains obscure. Here, we tested four skeletal protein extraction 20 protocols … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…We therefore sought to minimize the amount of material used for sequencing. Some modern coral skeletal proteome sequencing has used 10–30 g of cleaned skeleton powder 27 , 28 , but comparable protein detection can be obtained from approximately 1 g of cleaned modern material 29 . In this study, we found that this smaller amount of skeleton allowed sequencing of some fossil proteins and reinforces that these biomolecules are potentially available for sequencing from invertebrate biominerals aged over 100 ka.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore sought to minimize the amount of material used for sequencing. Some modern coral skeletal proteome sequencing has used 10–30 g of cleaned skeleton powder 27 , 28 , but comparable protein detection can be obtained from approximately 1 g of cleaned modern material 29 . In this study, we found that this smaller amount of skeleton allowed sequencing of some fossil proteins and reinforces that these biomolecules are potentially available for sequencing from invertebrate biominerals aged over 100 ka.…”
Section: Discussionmentioning
confidence: 99%
“…CARP4/SAARP1, CARP5/SAARP2, and P27/acidic SOMP/SAARP3, previously sequenced from coral skeletons 26 29 , were blasted against the cnidarian predicted protein databases in comparative.reefgenomics.org 35 . They were also blasted against NCBI and the top non-cnidarian hits with E-values better than e-20, two Crassostrea gigas sequences , were retained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In scleractinians, numerous SOM-related characteristics have been studied ( Tambutté et al, 2011 ), yet only a few proteomic profiling experiments have been conducted, and then solely for tropical species. Extensive proteomic studies using species-specific genomes and transcriptomes include those of Stylophora pistillata ( Drake et al, 2013 ; Peled et al, 2020 ), Acropora millepora ( Ramos-Silva et al, 2013 ), and Acropora digitifera ( Takeuchi et al, 2016 ), which, when combined, revealed over 100 SOM protein, hence members of the “biomineralization toolkit.” Similar to previous examinations of various metazoan lineages, scleractinian SOM proteins appear to share functional roles in carbohydrate-binding and catalytic activities ( Ramos-Silva and Marin, 2015 ). Notably, the most extensively studied SOM proteins in scleractinians are the aspartic acid-rich proteins which assist in mineral nucleation and modification ( Lowenstam and Weiner, 1989 ; Marin and Luquet, 2008 ; Mass et al, 2013 ; Gavriel et al, 2018 ; Laipnik et al, 2019 ), and α-carbonic anhydrases that play a role in both carbon supply and concentration ( Bertucci et al, 2013 ; Zoccola et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, many scleractinian SOM proteins do not contain known functional domains and remain to be functionally characterized. Furthermore, out of all the known scleractinian SOM proteins, only a few were found to be shared between the three species ( Takeuchi et al, 2016 ; Peled et al, 2020 ). The identification and characterization of the suite of scleractinian SOM proteins to date has led to the hypothesis that the proteins underlying scleractinian skeleton formation developed through stepwise evolution, supplementing proteins that are conserved across Metazoa with scleractinian-specific and species-specific novel proteins ( Ramos-Silva et al, 2013 ; Takeuchi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%